Developing Ethnomatematics-Based Flipbook in Circle Material at VIII Grade of Junior High School - Maghfiroh S. A. M. M; Agus Suharman; Rezky Ramadhona (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
Every ethnic group has various shapes, sizes, and cultural patterns that are interesting to study. Incorporating cultural elements in learning mathematics as the representation of ethnomatematics is helpful to introduce cultural values to the younger generation implicitly. The combination of technology and ethnomatematics for creating learning media should be tried because it contain a positive values for attracting students' learning interest. This study purposes to develop ethnomatematics-based flipbook in circle material at VIII grade of junior high school. The results show that ethnomatemics-based flipbook is appropriate to apply. The validation result of material experts is 80%, validation of media experts is 77%, and and from the student questionnaire responses is 74%.